Efektivitas Pelatihan Coping Stress Sebagai Upaya Mengurangi Stres Peran Pada Karyawan Di PT. Metal Hitech Engineering - Dinda Mila Duwi Rosalinda; Ima Fitri Sholichah (CV. ITTC INDONESIA, 2025)
Role Stress is a significant psychological risk factor in industrial settings, potentially leading to reduced work performance and poor employee well-being. This study aimed to investigate the efficacy of a Coping Stress Training program as an intervention to reduce the level of role stress experienced by employees at PT. Metal Hitech Engineering. This research employed a quasi-experimental design using a one-group pretest-posttest approach. The participants were employees as PT. Metal Hitech Engineering who had been identified as having moderate to high levels of role stress. Role stress levels were measured using a validated questionnaire administered during the pre-test and post-test phases. The data obtained were analyzed using the Paired Sample T-Test to compare mean scores before and after the intervention. The statistical analysis revealed a significant decrease (P < 0.05) in the mean role stress scores in the post-test condition compared to the pre-test scores. This substantial reduction demonstrates that the Coping Stress Training was effective in mitigating role-related pressure and stress among the participants. The Coping Stress Training is proven to be an effective psychological intervention for reducing role stress in employees. These findings underscore the importance of integrating psychological-based stress management programs into organizational health and safety initiatives to maintain optimal employee function and productivity.